Fathu Rabbani Sebagai Etika Digital: Tasawuf Abdul Qadir Al-Jailani Dalam Menghadapi Krisis Media Sosial - Yoga Adhitya Fredy Firmansyah; Fatya Eka Nurfaizah; Akhmal Raihan; Saharani Saharani (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2026)
The advancement of the digital era has shifted the way individuals form interactions, interpret information, and develop spiritual identity. Amid the widespread distractions, consumerist culture, and the diminishing depth of meaning caused by the use of social platforms, Sufism offers a soothing spiritual approach. Teachings such as sincerity, patience, and asceticism, as outlined in Fathu Rabbani, can function as strategies to preserve inner well‑being, manage emotions, and create more meaningful digital interactions. This line of thought contributes positive value as a moral and spiritual structure in facing the demands of the online world. However, the use of classical teachings still encounters various obstacles. The instant dynamics of social media, the tendency toward shallow online relationships, and the shifting values of society require a renewed reading of Sufi teachings in order to maintain their relevance. Classical references are often brief and do not explicitly address digital contexts, thus requiring contextual interpretation. In addition, not all individuals possess sufficient spiritual competence or digital understanding to consistently apply Sufi principles in online activities. The priority of this research lies in the need to present ethical guidelines capable of harmonizing digital advancement with the spiritual quality of individuals. By employing a qualitative method based on literature review, this study seeks to formulate a Sufism‑based digital ethical framework that can strengthen the spiritual life of Muslim communities while providing ethical direction in online interactions. Such an approach is crucial to ensure that religious practice remains relevant, contextual, and capable of responding to the ethical challenges of digital society.